Toll-Like Receptor 4 in Bone Marrow-Derived Cells Contributes to the Progression of Diabetic Retinopathy. (17th August 2014) - Wang, Hui; Shi, Haojun; Zhang, Jing; Wang, Guoliang; Zhang, Jinxiang; Jiang, Fagang; Xiao, Qing
Abstract : Diabetic retinopathy (DR) is a major microvascular complication in diabetics, and its mechanism is not fully understood. Toll-like receptor 4 (TLR4) plays a pivotal role in the maintenance of the inflammatory state during DR, and the deletion of TLR4 eventually alleviates the diabetic inflammatory state. To further elucidate the mechanism of DR, we used bone marrow transplantation to establish reciprocal chimeric animals of TLR4 mutant mice and TLR4 WT mice combined with diabetes mellitus (DM) induction by streptozotocin (STZ) treatment to identify the role of TLR4 in different cell types in the development of the proinflammatory state during DR. TLR4 mutation did not block the occurrence of high blood glucose after STZ injection compared with WT mice but did alleviate the progression of DR and alter the expression of the small vessel proliferation-related genes, vascular endothelial growth factor (VEGF), and hypoxia inducible factor-1 α (HIF-1 α ). Grafting bone marrow-derived cells from TLR4 WT mice into TLR4 mutant mice increased the levels of TNF- α, IL-1 β, and MIP-2 and increased the damage to the retina. Similarly, VEGF and HIF-1 α expression were restored by the bone marrow transplantation. These findings identify an essential role for TLR4 in bone marrow-derived cells contributing to the progression of DR.